AKUNTABILITAS PELAPORAN WAKAF BERDASARKAN PSAK SYARIAH - Suparji Suparji (Jurnal Magister Ilmu Hukum, 2019)
ABSTRAKS-Waqf Accountability is a form of nadzir accountability in reporting management of waqf to stakeholders, one form of accountability is financial statements in accordance with generally accepted accounting standards about waqf, where all this time waqf reporting still uses Statement of Islamic Financial Accounting Standards No. 109 concerning Zakat, Infaq and Shodaqah No. 109 concerning Zakat, Infaq and Shodaqah. Where besides being fulfilled accountability also must be able to help the government in alleviating poverty through the distribution of waqf benefits to Mustafa alaih, but the role of waqf in the welfare of the nation has not been maximized due to the lack of optimal use of waqf management due to limited financial access and lack of knowledge in management of waqf and the synergy between the parties concerned has not been maximized. Formulation of the problem in this study, How to implement waqf arrangements in financial reporting at the Waqf Institution. The method used in this study is normative juridical, where the author conducts an analysis based on the laws and regulations associated with the related legal theory. The theory used is welfare theory and economic analysis of laws. Application of PSAK Syariah No. 109 so that there needs to be a PSAK that complies with waqf accounting reporting standards can be more accountable.Keywords: Accountability, Reporting, Accounting for Endowments